ANALISIS KASUS MAL ADMINISTRASI DI OMBUDSMAN RI PERWAKILAN KALIMANTAN SELATAN TAHUN 2013-2015 - Abdul Haliq; Umar Makawi; Normajatun Normajatun (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2017)
This research is intended to know the level of public complaints to public service to the Ombudsman of the Republic of Indonesia representative of South Kalimantan Province, the period of 2013 - 2015. In addition to knowing the obstacles of the Ombudsman Institution of the Republic of Indonesia Representative of South Kalimantan Province In following up or resolve complaints community. The method used is the approach of quantitative and qualitative research, with the form of data collection through the database. While data analysis using Model Miles and Huberman, using phase, Data Reduction, Data Display, and Conclusion Drawing / verification. The results show maladministration case between the years 2013-2015, the most frequent reporter is individual / direct victim and occurred in 2015 that is 71 cases (61%), from classification reported from year to year continue to increase this happened to city government / regency, And the most prevalent in 2015 ie 77 cases (66.4%). Meanwhile, when viewed from the type of maladministration of the most reported public reported is in the year 2013 is a case of delayed soluble, whereas in 2014-2015 cases do not provide services, and the case is most prevalent in 2014 ie 51 cases (38.3% ), Whereas by 2015 this case has declined.